Sasak language speech codes in various communication context: An ethnographic study by Dell Hymes - Mas'ud, Lalu; Fakihuddin, Lalu; Wijaya, Herman; Setiyoningsih, Titi (Universitas Ahmad Dahlan, 2026)
This study reveals the use and negotiation of base alus (BA) and base jamaq (BJ) speech codes in the family, social, economic, and institutional spheres, and describes their sociopragmatic functions and the factors that influence their shifts. The method used was qualitative with an ethnographic approach to communication based on Dell Hymes' SPEAKING model. Data was collected through observation and interviews, analysed through reduction, presentation and conclusion drawing, and validated through triangulation and member checking. The results of the study found that BA persisted as a polite form of speech among the aristocracy in family and social circles. In the economic sphere, BJ–BA is chosen based on social status and closeness, while also regulating the